Severe Vitamin B12 Deficiency in Pregnancy Mimicking HELLP Syndrome - Shravya Govindappagari; Michelle Nguyen; Megha Gupta; Ramy M. Hanna; Richard M. Burwick (Case Reports in Obstetrics and Gynecology)
Severe vitamin B12 deficiency may present with hematologic abnormalities that mimic thrombotic microangiopathy disorders such as hemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome. We report a patient diagnosed with severe vitamin B12 deficiency, following termination of pregnancy for suspected preeclampsia and HELLP syndrome at 21 weeks’ gestation. When hemolysis and thrombocytopenia persisted after delivery, testing was performed to rule out other etiologies of thrombotic microangiopathy, including atypical hemolytic uremic syndrome, thrombotic thrombocytopenic purpura, and vitamin B12 deficiency. This work-up revealed undetectable vitamin B12 levels and presence of intrinsic factor antibodies, consistent with pernicious anemia. Parenteral B12 supplementation was initiated, with subsequent improvement in hematologic parameters. Our case emphasizes the importance of screening for B12 deficiency in pregnancy, especially in at-risk women with unexplained anemia or thrombocytopenia. Moreover, providers should consider B12 deficiency and pernicious anemia in the differential diagnosis of pregnancy-associated thrombotic microangiopathy.